Phosphate intake and removal in predominantly vegetarian patients on twice-weekly hemodialysis - Rao, Namrata; Chandra, Abhilash; Kulshreshta, Manish; Tiwari, Poonam; Saran, Sai; Lohiya, Ayush (Indian journal of nephrology, 2022)
Background: Hyperphosphatemia is linked to increased mortality and morbidity in patients on hemodialysis. Currently, the phosphate intake and dialytic removal in predominantly vegetarian patients on twice-weekly dialysis is not well studied. Materials and methods: This prospective, study recruited patients on twice-weekly dialysis of at least 3 months duration. Baseline clinical variables were measured. Dietary protein and phosphorus intake was assessed using a validated food frequency questionnaire. Phosphate binder use was assessed, hourly blood was collected for serum phosphorus during dialysis, and spent dialysate was collected to estimate cumulative phosphorus removal during the session. Results: Forty (67%) of the 60 patients studied were vegetarians. Twenty-eight (48%) were hyperphosphatemic, and 15 (25%) had serum parathormone (PTH) >500 pg/ml. The mean phosphorus intake was 1247 (±312) mg/day, the mean serum phosphorus was 5.49 (±2.01) mg/dl, and the mean dialytic phosphorus removal was 910 (±383) mg/session. Up to 67% of the study population took calcium-based phosphate binders, 25% took sevelamer carbonate, and 40% took activated vitamin D preparation. The lowest tertiles of phosphorus intake correlated with low energy-adjusted protein intake and hypoalbuminemia. Hyperphosphatemic subjects had better nutritional indices (mid-upper arm circumference and body mass index). Dietary intake and serum phosphorus levels were not mutually associated, but both were strongly correlated with total phosphorus removal in the spent dialysate. Serum phosphorus levels fell by 32% by the first hour of hemodialysis. Conclusion: Twice-weekly dialysis is often practised in resource-limited Asian countries. However, due to a predominantly vegetarian diet, hyperphosphatemia was noted only in up to half of the patients, despite twice-weekly hemodialysis schedules. This reinforces the fact that plant-based dietary phosphate is less well absorbed.